POLA IMPLEMENTASI TEORI KONSTRUKTIVISME PADA PEMBELAJARAN TATAP MUKA TERBATAS DI SEKOLAH DASAR - Beti Istanti Suwandayani; Kuncahyono; Ade Ika Anggraini (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aimed to examine the implementation pattern of the constructivist theory in limited face-to-face learning (PTMT). The method used was descriptive qualitative with the subject of teachers in the Malang City area. Data was collected by using a survey distributed online through Google Forms. The results showed that the implementation pattern ofconstructivist theory in limited face-to-face learning (PTMT) was carried out through 5 (five) base of learning implementation, namely the application of problem-based learning, the application of project-based learning, the use of digital-based teaching materials and media, the application of psychosocial learning and contextuallearning. Teachers carried out limited face-to-face learning by applying constructivist theory massively and gradually, starting from planning, the process of learning activities, and learning evaluation. In addition to the use of media and 5M learning models in this study, the application of constructivist theory in PTMT learning aimed to help students become more active and teachers as moderators be more innovative. Learning process carried out at the elementary school level was only 50 percent attendance at the maximum. The implementation of student-centered learning showed 45% was very good, 50% was good, 2.5% was good, 2.5% was not good. The results showed that the inhibiting factor for student-centered implementation was the limited duration of time in learning. On the other hand, there were also restrictions on interactions carried out in the classroom so that teachers experienced a decline in exploring the learning process. Keywords: constructivism theory. limited face-to-face learning, elementary school. References: Adiyono, A. 2021. Implementasi Pembelajaran: Peluang dan Tantangan Pembelajaran Tatap Muka Bagi Siswa Sekolah Dasar di Muara Komam. Edukatif: Jurnal Ilmu Pendidikan, 3(6), 5017–5023. Al Hakim, R.T.Y. 2021. Pembelajaran Online di Tengah Pandemi Covid-19, Tantangan yang Mendewasakan. Pembelajaran Online Di Tengah Pandemi Covid-19, Tantangan Yang Mendewasakan (Antologi Esai Mahasiswa Pendidikan Bahasa Inggris), 1. Alawamleh, M., Al-Twait, L.M., & Al-Saht, G. R. 2020. The effect of online learning on communication between instructors and students during Covid-19 pandemic. Asian Education and Development Studies. https://doi.org/10.1108/AEDS-06-2020-0131 Anam, C. 2021. Analisis Kesiapan Pendidikan Vokasi Dalam Menyongsong Pembelajaran Tatap Muka Di Masa Pandemi Covid 19 (Studi Kasus di LP3I Malang). Jurnal Vokasi, 5(2), 112–118. Ananda, R., Fadhilaturrahmi, F., & Hanafi, I. 2021. Dampak Pandemi Covid-19 terhadap Pembelajaran Tematik di Sekolah Dasar. Jurnal Basicedu, 5(3), 1689–1694. Barnová, S. 2020. The impact of Covid-19 pandemics on schools – challenges and new opportunities for a woman-owned organization. Journal Women’s Entrepreneurship and Education, 2020(3), 41–58. https://doi.org/10.28934/jwee20.34.pp41-58 Chalkiadaki, A. 2018. A Systematic Literature Review of 21 st Century Skills and Competencies in Primary Education. International Journal of Instruction, 11(3), 1–16. Chaturvedi, K., Vishwakarma, D.K., & Singh, N. 2021. COVID-19 and its impact on education, social life and mental health of students: A survey. Children and Youth Services Review, 121(July 2020), 105866. https://doi.org/10.1016/j.childyouth.2020.105866 Dewi, L., & Fauziati, E. 2021. Pembelajaran Tematik di Sekolah Dasar dalam Pandangan Teori Konstruktivisme Vygotsky. Jurnal Papeda: Jurnal Publikasi Pendidikan Dasar, 3(2), 163–174. Dewi, W.A.F. 2020. Dampak COVID-19 terhadap Implementasi Pembelajaran Daring di Sekolah Dasar. Edukatif : Jurnal Ilmu Pendidikan, 2(1), 55–61. https://doi.org/10.31004/edukatif.v2i1.89 Donthu, N., & Gustafsson, A. 2020. Effects of COVID-19 on business and research. Elsevier. Esterwood, E., & Saeed, S.A. 2020. Past Epidemics, Natural Disasters, Covid19, and Mental Health: Learning from History as we Deal with the Present and Prepare for the Future. Psychiatric Quarterly, 91(4), 1121–1133. https://doi.org/10.1007/s11126-020-09808-4 Fernandes, R., Ananda, A., Montessori, M., Firman, F., Putra, E. V., Naldi, H., & Fitriani, E. 2021. Adaptasi Dosen Digital Immigrant Terhadap Pelaksanaan Pembelajaran pada Masa Pandemi Covid-19. Jurnal Socius: Journal of Sociology Research and Education, 8(1), 59–72. Fitri, M. 2020. Pengaruh Emergency Remote Learning Untuk Melihat Motivasi Belajar Anak Usia Dini. Child Education Journal, 2(2), 68–82. Ghosh, R. 2020. Impact of Covid-19 on children: Special focus on the psychosocial aspect. In Minerva Pediatrica (Vol. 72, Issue 3, pp. 226–235). https://doi.org/10.23736/S0026-4946.20.05887-9 Gleason, N.W. 2018. Higher Education in the Era of the Fourth Industrial Revolution. In Higher Education in the Era of the Fourth Industrial Revolution. https://doi.org/10.1007/978-981-13-0194-0 Gusty, S., Nurmiati, N., Muliana, M., Sulaiman, O. K., Ginantra, N. L. W. S. R., Manuhutu, M. A., Sudarso, A., Leuwol, N. V., Apriza, A., & Sahabuddin, A. A. (2020). Belajar Mandiri: Pembelajaran Daring di Tengah Pandemi Covid-19. Yayasan Kita Menulis. Husna, M., & Sugito, S. 2021. Eksplorasi Penerapan Pembelajaran Tatap Muka Terbatas pada Jenjang PAUD di Masa Kebiasaan Baru. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 6(3), 1846–1858. Khan, A. 2017. Active learning: Engaging students to maximize learning in an online course. Electronic Journal of E-Learning, 15(2), 107–115. Khattar, A., Jain, P.R., & Quadri, S.M.K. 2020. Effects of the Disastrous Pandemic Covid 19 on Learning Styles, Activities and Mental Health of Young Indian Students-A Machine Learning Approach. Proceedings of the International Conference on Intelligent Computing and Control Systems, ICICCS 2020, Iciccs, 1190–1195. https://doi.org/10.1109/ICICCS48265.2020.9120955 Kuo, Y. C., Walker, A.E., Schroder, K.E.E., & Belland, B. R. 2014. Interaction, Internet self-efficacy, and self-regulated learning as predictors of student satisfaction in online education courses. Internet and Higher Education, 20, 35–50. https://doi.org/10.1016/j.iheduc.2013.10.001 Lai, A.Y. kwan, Lee, L., Wang, M.P., Feng, Y., Lai, T.T. kwan, Ho, L. M., Lam, V. S. fun, Ip, M. S. man, & Lam, T. H. 2020. Mental Health Impacts of the Covid-19 Pandemic on International University Students, Related Stressors, and Coping Strategies. Frontiers in Psychiatry, 11(November). https://doi.org/10.3389/fpsyt.2020.584240 Lamb, J., & Lamb, W.A. 1975. Parent Education and Elementary Counseling. Lase, D., Ndraha, A., & Harefa, G.G. 2020. Persepsi Orangtua Siswa Sekolah Dasar di Kota Gunungsitoli Terhadap Kebijakan Pembelajaran Jarak Jauh pada Masa Pandemi Covid-19. SUNDERMANN: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora Dan Kebudayaan, 13(2), 85–98. Lyu, K. 2020. The implementation and effectiveness of intergenerational learning during the Covid-19 pandemic: Evidence from China. International Review of Education, 66(5), 833–855. https://doi.org/10.1007/s11159-020-09877-4 McEachin, A., & Atteberry, A. 2016. The Impact of Summer Learning Loss on Measures of School Performance. The Impact of Summer Learning Loss on Measures of School Performance. https://doi.org/10.7249/wr1149 Miles, M.B., & Huberman, A.M. 1994. Qualitative data analysis: An expanded sourcebook. sage. Mohammadyari, S. 2015. Understanding the effect of e-learning on individual performance: The role of digital literacy. Computers and Education, 82, 11–25. https://doi.org/10.1016/j.compedu.2014.10.025 Nam, C. 2017. The effects of digital storytelling on student achievement, social presence, and attitude in online collaborative learning environments. Interactive Learning Environments, 25(3), 412–427. https://doi.org/10.1080/10494820.2015.1135173 Nissa, S.F., & Haryanto, A. 2020. Implementasi Pembelajaran Tatap Muka Di Masa Pandemi Covid-19. Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 8(2), 402–409. Nuraini, H. 2021. Perjalanan Menuju Kebermaknaan Hidup Bersama PandemI. Nurkhasanah, E. 2020. Menyoal Pandemi Global Pada Pergeseran Pembelajaran Klasikal. Minda Guru Indonesia: Guru Dan Pembelajaran Inovatif Di Masa Pandemi Covid-19, 39. Okada, A. 2019. e-Authentication for online assessment: A mixed-method study. British Journal of Educational Technology, 50(2), 861–875. https://doi.org/10.1111/bjet.12608 Pane, A., & Dasopang, M.D. 2017. Belajar dan pembelajaran. Fitrah: Jurnal Kajian Ilmu-Ilmu Keislaman, 3(2), 333–352. Puncreobutr, V. 2016. Education 4.0: New challenge of learning. St. Theresa Journal of Humanities and Social Sciences, 2(2). Rahayu, G. D. S. 2020. Analysis of elementary school students’ mathematical resilience during learning during the COVID 19 Pandemic. In Journal of Physics: Conference Series (Vol. 1657, Issue 1). https://doi.org/10.1088/1742-6596/1657/1/012001 Rangkuti, A.N. 2014. Konstruktivisme dan Pembelajaran Matematika. Darul Ilmi: Jurnal Ilmu Kependidikan Dan Keislaman, 2(2). Rasmitadila. 2020. The perceptions of primary school teachers of online learning during the Covid-19 pandemic period: A case study in Indonesia. Journal of Ethnic and Cultural Studies, 7(2), 90–109. https://doi.org/10.29333/ejecs/388 Roche, M. 2016. PBL trigger design by medical students: An effective active learning strategy outside the classroom. Journal of Clinical and Diagnostic Research, 10(12). https://doi.org/10.7860/JCDR/2016/21813.9015 Rozzaqyah, F. 2020. Urgensi Konseling Krisis dalam Menghadapi Pandemi Covid-19 Di Indonesia. Prosiding Seminar Bimbingan Dan Konseling, 136–143. Sanjaya, R. 2020. 21 Refleksi Pembelajaran Daring di Masa Darurat. SCU Knowledge Media. Siahaan, M. 2020. Dampak pandemi Covid-19 terhadap dunia pendidikan. Dampak Pandemi Covid-19 Terhadap Dunia Pendidikan, 20(2). Simanjuntak, M.F., & Sudibjo, N. 2019. Meningkatkan Keterampilan Berpikir Kritis Dan Kemampuan Memecahkan Masalah Siswa Melalui Pembelajaran Berbasis Masalah [Improving Students’ Critical Thinking Skills and Problem Solving Abilities Through Problem-Based Learning]. JOHME: Journal of Holistic Mathematics Education, 2(2), 108. https://doi.org/10.19166/johme.v2i2.1331 Simatupang, M.S., & Peter, R. 2020. Pergeseran Pembelajaran di Masa Pandemi. Suparlan, S. 2019. Teori Konstruktivisme dalam Pembelajaran. ISLAMIKA, 1(2), 79–88. Supriyanto, A., Rozaq, J.A., Santosa, A.B., & Listiyono, H. 2021. Uji Coba Persiapan Pembelajaran Tatap Muka Masa Normal Baru PAUD “Tunas Bangsa” Semarang. Jurnal Pengabdian Pada Masyarakat, 6(3), 753–763. Tanuwijaya, N.S., & Tambunan, W. 2021. Alternatif Solusi Model Pembelajaran Untuk Mengatasi Resiko Penurunan Capaian Belajar Dalam Pembelajaran Tatap Muka Terbatas Di Masa Pandemic Covid 19. Jurnal Manajemen Pendidikan, 10(2), 80–90. Turner, K.L., Hughes, M., & Presland, K. 2020. Learning Loss, a Potential Challenge for Transition to Undergraduate Study following COVID19 School Disruption. Journal of Chemical Education, 97(9), 3346–3352. https://doi.org/10.1021/acs.jchemed.0c00705 Ullah, R., Rana, M.S., Qadir, M., Usman, M., & Ahmed, N. 2021. Coronavirus Pandemic: a major public health crisis for the developed and developing world. The Journal of Infection in Developing Countries, 15(03), 366–369. Wachyuni, S.S., & Kusumaningrum, D.A. 2020. The effect of COVID-19 pandemic: How are the future tourist behavior? Journal of Education, Society and Behavioural Science, 67–76. Woolf, S.H., Masters, R.K., & Aron, L.Y. 2021. Effect of the Covid-19 pandemic in 2020 on life expectancy across populations in the USA and other high income countries: simulations of provisional mortality data. Bmj, 373.